Development of a nursing outcome for a percutaneous procedure. Issue 2 (9th June 2021) - Reich, Rejane; Rabelo‐Silva, Eneida Rejane; Swanson, Elizabeth; Moorhead, Sue; Almeida, Miriam de Abreu
ABSTRACT: Objectives: To develop a nursing outcome, consistent with the standardized format of outcomes within the nursing Outcomes Classification (NOC). This outcome will include an outcome label, an outcome definition, and clinical indicators. The proposed use for this outcome is to evaluate the access site of a percutaneous procedure. Methods: Concept analysis with a scoping review. Initially, content experts were recruited to validate the indicators of the proposed outcome in order to complete a consensus validation. After consensus validation, a review of the proposed outcome and its indicators was completed by two of the editors of the NOC team to confirm that the outcome label, definition, and indicators were consistent with the NOC taxonomy. During this review, edits were made on the label name and definition. Findings: After a series of reviews, the initial outcome of Vascular Status : Percutaneous Procedure Access was changed to Tissue Injury Severity: Percutaneous Procedure . In addition, the original definition of the condition of an access site for percutaneous procedure by venous or arterial puncture and health of surrounding tissues was edited to: Severity of complications from a needle‐puncture access through the skin and into deeper tissues. The outcome has 11 indicators to be used to formulate a target rating for use in the clinical setting. The indicators were not edited over the course of the reviews. Conclusion: The proposed outcome will assist nurses in evaluating the access site of percutaneous procedures and in identifying possible complications. Implications for the Nursing Practice: This research contributes to the refinement of the NOC taxonomy by having a new outcome that meets clinical practice needs. Abstract : Objetivos: Desenvolver um resultado de enfermagem, consistente com o formato padronizado de resultados da Classificação dos Resultados de Enfermagem (NOC). Este resultado incluirá um título de resultado, uma definição de resultado e indicadores clínicos. O uso proposto para esse resultado é avaliar o local de acesso de um procedimento percutâneo. Métodos: Análise de conceito com revisão de escopo. Inicialmente, especialistas de conteúdo foram utilizados para validar os indicadores do resultado proposto em uma validação por consenso. Após a validação por consenso, uma revisão do resultado proposto e de seus indicadores foi realizada por dois editores da equipe da Classificação dos Resultados de Enfermagem para confirmar o título do resultado, definição e indicadores para serem consistentes com a taxonomia NOC. Durante esta revisão, foram feitas edições no título e na definição. Resultados: Após uma série de revisões, o resultado denominado inicialmente de Estado Vascular: Acesso Procedimento Percutâneo foi alterado para Gravidade da Lesão Tecidual: Procedimento Percutâneo. Além disso, a definição original de condição de um local de acesso de procedimento percutâneo por punção venosa ou arterial e saúde dos tecidos adjacentes foi editada para – Gravidade das complicações de um acesso por punção com agulha através da pele e em tecidos mais profundos. O resultado tem 11 indicadores a serem usados para formular uma classificação‐alvo para uso no ambiente clínico. Os indicadores não foram editados ao longo das revisões. Conclusão: O resultado proposto auxiliará o enfermeiro a avaliar o local de acesso dos procedimentos percutâneos e identificar possíveis complicações. Implicações para a prática de enfermagem: Esta pesquisa contribui para o refinamento da taxonomia NOC por ter um novo resultado que atende às necessidades da prática clínica.